PERBANDINGAN HUKUM PIDANA TENTANG UJARAN KEBENCIAN DI INDONESIA, MALAYSIA DAN NORWEGIA - Hartanto, Hartanto; Syakdiah, Syakdiah; Malkhi, Yusuf (HUKMY : Jurnal Hukum, 2024)
Hate speech is an issue that is still interesting to study, because each country's Criminal Code regulates this matter. Hate speech can also be found in various media, including through activity speeches, pamphlets or social media, public speeches (demonstrations), religious lectures, printed mass media, and pamphlets. factors, such as education, culture, and social. Based on the description above, the authors chose the title of comparative legal research on hate speech according to Indonesian criminal law (KUHP), Malaysian criminal law and Norwegian criminal law. This type of research is normative juridical research by examining literature or secondary materials by referring to legal norms contained in statutory regulations, as well as other legal literature. The approach used is comparative, to then be analyzed and concluded. From the results of the data analysis, it can be concluded that the provisions on hate speech in the Indonesian, Malaysian and Norwegian Criminal Codes have similarities in terms of the concept of hate speech, although they are not exactly the same, while the difference is in the implementation and legal sanctions.